Alien Species Alert: Ensis directus Current status of invasions by the marine bivalve Ensis directus - Gollasch, S; Kerckhof, F; Craeymeersch, J; Goulletquer, Philippe; Jensen, K; Jelmert, A; Minchin, D (ICES, 2015)
The North American bivalve mollusc Ensis directus (Conrad, 1843) (Bivalvia, Pharidae) is native to the Northwest Atlantic coasts from southern Labrador to northern Florida (Bousfield, 1960; Theroux and Wigley, 1983; Swennen et al., 1985; Abbott and Morris, 2001; Turgeon et al., 2009; Vierna et al., 2013). This species has been introduced outside its native range, with the first confirmed record from the German Bight in 1979 (Cosel et al., 1982). Thereafter, a subsequent secondary range expansion took place, and the species is presently known to occur from Spain to Norway, including the UK (e.g. Mühlenhardt- Siegel et al., 1983; Essink, 1985, 1986; Kerckhof and Dumoulin; 1987, Luczak et al., 1993; Rasmussen, 1996; Brattegard and Holthe, 1997; Eno et al., 1997; Severijns, 2000, 2002, 2004; Wolff, 2005; Dauvin et al., 2007; Houziaux et al., 2011; Arias and Anadon, 2012; Dannheim and Rumohr, 2012; Witbaard et al., 2013) and in the western Baltic (Gürs et al., 1993). The most recent expansion was to the Bay of Biscay (Arias and Anadon, 2012) from where it may be expected to spread further. E. directus has all the characteristics of a successful “r” strategist invader, including high reproductive capacity, short generation time, and rapid growth. Its expansion is principally due to natural dispersal. It usually occurs in clusters and has wide environmental tolerances (Dannheim and Rumohr, 2012). Moreover, its native predators (e.g. the snail Polinices heros and the nemertean Cerebratulus lacteus) are absent in Europe (Cosel, 2009). Although E. directus is common in its native range, it is more abundant in its introduced range. Further, its exceptional colonization success in Europe is likely related to its use of underutilized tidal habitats that are characterized by exposure to physical disturbance as a consequence of wave action and strong tidal currents. It appears that E. directus is one of the few larger benthic invertebrates able to tolerate the unstable sands in the tidal zone (Dekker and Beukema, 2012). ...